Empowerment without Emancipation: Performativity and Political Activism among Iranian Refugees in Italy and Turkey - Rivetti, Paola (Alternatives: global, local, political, 2013)
This article examines the centrality of political activism in the identity of Iranian refugees and investigates how they perform and incorporate it by considering the interlocked pressure of international politics, personal networks, and the assistance provided by civil society organizations. The case of Iranian political refugees in Italy and Turkey is of particular interest because of the international visibility of the Green movement, the Iranian people's historical experience of emigration, and the fact that Iran is a subject of great interest for a number of human rights non-governmental organizations (NGOs). It shows how the process of "being a refugee" works not only through classical forms of institutional pressure but also through "unexpected" forms such as NGO efforts to empower refugees politically. Despite the positive value attached to it, in this context political activism can force refugees into preestablished roles, such as "human rights defenders" or "Green movement activists." Paradoxically, refugees act within a context that dominates them even when it tries to empower them.